2017
DOI: 10.1002/cncy.21886
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of EBUS‐TBNA cytology in the staging of mediastinal lymph nodes in lung cancer patients: A correlation study with positron emission tomography findings

Abstract: BACKGROUND:The sensitivity and specificity of positron emission tomography (PET) have been significantly improved for the identification of malignancies in recent years; however, it is still necessary to confirm PET findings in a lymph node (LN) by direct tissue sampling. Endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) is the most commonly used approach for diagnosing and staging mediastinal LNs, particularly in lung cancer patients with locally advanced disease. Despite this fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In view o f t h e l o w i n v a s i v e n e s s , E B U S -T B N A m a y b e recommended as a complementary examination to the imaging study. Lilo et al (35) reported the results of EBUS-TBNA on 70 patients previously subjected to 18 F-FDG-PET/CT for the study of lymph nodes. Of 140 lymph nodes considered, 54 were negative to 18 F-FDG-PET/CT while the subsequent use of EBUS-TBNA allowed identifying 4 (7%) lymph nodes that possessed signs of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In view o f t h e l o w i n v a s i v e n e s s , E B U S -T B N A m a y b e recommended as a complementary examination to the imaging study. Lilo et al (35) reported the results of EBUS-TBNA on 70 patients previously subjected to 18 F-FDG-PET/CT for the study of lymph nodes. Of 140 lymph nodes considered, 54 were negative to 18 F-FDG-PET/CT while the subsequent use of EBUS-TBNA allowed identifying 4 (7%) lymph nodes that possessed signs of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Only 65 of 314 lymph nodes (21%; Figure 5, B) in the PET-CTþ/CytoÀ group had significant cytologic findings of infection, acute inflammation, necrosis, or granulomatous inflammation, including 3 patients with fungal organisms identified on smears. Similarly, Lilo et al 14 reported that 36 of 86 PETþ lymph nodes (41.8%) were negative for malignancy and 25% of benign lymph nodes had granulomas. Other small case series have described increased FDG uptake in benign conditions, most of which are granulomatous inflammation including sarcoidosis, infection, pneumonitis, previous pulmonary tuberculosis, and silicosis.…”
Section: Discussionmentioning
confidence: 86%
“…PET-CT is a noninvasive imaging modality commonly used as the initial step in clinical staging for cancer patients as well as for restaging cancer patients after treatment. 13,14 However, the overlap in SUV/FDG-avidity between benign and malignant conditions, 15,16 as well as high prevalence of inflammation/infection within mediastinal lesions with increased uptake of FDG [17][18][19] in thoracic lesions, has encouraged cytologic sampling by a minimally invasive modality, EBUS-TBNA for PET-CTþ lymph nodes. 20,21 In this study, we retrospectively compared the PET-CTþ/Cytoþ versus PET-CTþ/CytoÀ mediastinal lymph nodes sampled by EBUS-TBNA in patients with primary lung cancer, nonlung cancer, and patients with no known malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Although positive capsule is regarded as a potential indicator of PORT, further validation would be essential, because paradoxical results from another study suggested that PORT could only benefit those without extracapsular invasion. 30 In recent studies, EBUS-TBNA showed an increased capacity in detecting the eventual presence of extracapsular extension, 31 , 32 making it possible to investigate neoadjuvant radiotherapy in pre-surgically diagnosed extracapsular disease.…”
Section: Discussionmentioning
confidence: 99%